Autocratic Genderwashing: Gender‐Equality Reforms in Serbia - Lončar, Jelena (2024)
While gender equality is usually linked with democracy, autocratic regimes frequently take the lead in such reforms. Focusing on the case of Serbia, this article demonstrates how gender equality reforms can be used as instruments of autocratic regimes. As electoral autocracies nowadays depend on international legitimation and support, they need to present a democratic image to the international audience. Very often they achieve this by introducing gender-sensitive policies and increasing the public visibility of women. This study shows that the democratic backsliding evidenced in Serbia since 2016 has been followed by increased attention to gender equality. In recent years, the Serbian parliament has increased the gender quota for national and local parliaments to 40% and passed several important pieces of legislation, including the Law on Prevention of Domestic Violence (2016) and the Gender Equality Law (2021). Additionally, the regime has appointed a record number of women to executive government positions. Since 2017, Serbia has had a lesbian woman serving as a prime minister and the government formed in 2020 was labelled a “women’s government,” with 40% of ministerial positions held by women. This article argues that the regime tends to adopt these democratic reforms while, at the same time, manipulating their meaning to advance a conservative agenda and bolster anti-gender mobilizations. These different—often contradictory—strategies help the regime address a variety of audiences—both international and domestic—and gain their recognition.